2020
DOI: 10.3390/ijms21093221
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and Growth Factor Delivery from Implanted Platelet-Rich Fibrin Enhances Rabbit Achilles Tendon Healing

Abstract: Tendons are hypocellular and hypovascular tissues, and thus, their natural healing capacity is low. In this study, we sought to evaluate the efficacy of platelet-rich fibrin (PRF) to serve as a bioactive scaffold in promoting the healing of rabbit Achilles tendon injury. For in vitro study, the essence portion of PRF was determined through bioluminescent assay. Furthermore, we analyzed the time-sequential cytokines-release kinetics of PRF and evaluated their effects on tenocytes proliferation and tenogenic gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Further, gene expression analyses revealed the significant increase in COL1A1 and COL3A1 mRNA expression in the bPRF-treated groups. Corresponding to previous studies, PRF enhanced COL1A1 and COL3A1 mRNA expression in rabbit tenocytes in vitro [37]. Type III collagen is predominant in the proliferative phase of wound healing and is replaced by type I collagen.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Further, gene expression analyses revealed the significant increase in COL1A1 and COL3A1 mRNA expression in the bPRF-treated groups. Corresponding to previous studies, PRF enhanced COL1A1 and COL3A1 mRNA expression in rabbit tenocytes in vitro [37]. Type III collagen is predominant in the proliferative phase of wound healing and is replaced by type I collagen.…”
Section: Discussionsupporting
confidence: 79%
“…The role of PRF in soft tissue healing has previously been reported. PRF accelerated epithelialization and lessened scar formation in canine cutaneous incisional wound healing [37]. PRF also stimulated collagen-related protein expression compared with untreated controls [38].…”
Section: Discussionmentioning
confidence: 84%
“…Research by Kishimoto et al ( 2017 ) reported that activation of Wnt/β-catenin signaling suppressed expressions of tenogenic genes of Scleraxis (Scx), Mohawk (Mkx), and Tenomodulin (Tnmd) in rat tendon–derived cells isolated from the Achilles tendons of 6-week-old rats. All three genes are vital for tendon development, maintenance, and regeneration ( Yang et al, 2019 ; Wong et al, 2020 ; Best et al, 2021 ). This suggests that an inhibition of Wnt/β-catenin signaling may represent a novel therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…The local application of combined ascorbic acid and T 3 also showed the potential benefits for accelerated tendon healing (Oliva, et al, 2019). Platelet-rich fibrin (PRF), with the delivery of cytokine and growth factor, induced more organized collagen fibers in vivo and promoted tenocyte viability and tenogenic phenotypic differentiation in vitro (Wong, et al, 2020). Similarly, plateletrich plasma (PRP) is widely used and has been proven to be effective for tendon healing in vivo (Chiou, et al, 2015).…”
Section: Strategies For Achilles Tendon Repairmentioning
confidence: 99%